'Material likely to harm or disturb them': testing the alignment between film and game classification decisions and psychological research evidence. Issue 1 (2nd January 2022) - Handsley, Elizabeth; Warburton, Wayne
Abstract : This article analyses the practical operation of Australia's National Classification System (NCS) for films and games, to evaluate its alignment with the findings of psychological research. 1 Twenty-nine decisions of the Classification Review Board are examined to determine the factors applied in assessing the impact of violent content and drawing the line between the different classification categories. The language used in referring to violent content is analysed to determine the concepts that influence the Board's view about the correct classification. These concepts are then tested against the research evidence on the depictions of violence that create the greatest risk of adverse outcomes for viewers and players. Not all of the concepts used in classification have a basis in the research evidence, and some are directly at odds with that evidence. The article concludes by recommending changes to the rules that could lead to better alignment between classification decisions and the research evidence.